French de and en as expressions of the genitive case: a unified analysis within LFG and computational implementation in XLE1 - Alencar, Leonel Figueiredo de; Schwarze, Cristoph (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2022)
The French clitic pro-form en represents a wide range of heterogeneous constituents: de-PP complements and adjuncts, partitive objects, and prepositionless objects of cardinals. The main goal of this paper is to formalize this relationship computationally in terms of genitive case. This is apparently the first non-transformational counterpart to Kayne (1975)’s unified analysis, which derives en from a deep structure with de by means of syntactic transformations. Transformational grammars are problematic from the parsing perspective. In order to test our analysis automatically on a large amount of data, we implemented it in a computational grammar of French in the Lexical-Functional Grammar (LFG) formalism using the XLE system. This non-transformational framework is particularly fit for expressing systematic relationships between heterogeneous structures and has successfully been used for the implementation of natural language grammars since the 1980s. We tested the implementation on 320 grammatical sentences and on an equal number of ungrammatical examples. It analyzed all grammatical examples and blocked almost 95% of the ungrammatical ones, showing a high empirical adequacy of the grammar.